A new species of the genus Downsiomyia Vargas (Diptera: Culicidae) from Himachal Pradesh, India - Natarajan, R.; Gopalakrishnan, S.; Kumar, Pradeep; Kumar, Ashwani (Zootaxa, 2022)
The adult, larval and pupal stages of Downsiomyia rajaveli, a new species (Diptera: Culicidae) from India, are described and illustrated, and the mitochondrial COI barcode is provided for the species. The morphological relationship of the new species to other members of the genus Downsiomyia is discussed.